1998
DOI: 10.1123/apaq.15.2.119
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Effects on Health-Related Physical Fitness of Individuals with an Intellectual Disability: A Meta-Analysis

Abstract: A meta-analysis was conducted to determine the effects of exercise on health-related physical fitness of individuals with an intellectual disability. The data came from 21 individual studies yielding 100 effect sizes (ESs). Large effects were demonstrated for muscular and cardiovascular endurance, moderate for muscular strength, and small for flexibility. No significant effects were found for body composition. Document source and program length influenced muscular and cardiovascular endurance outcomes, as publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
27
0
7

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 0 publications
4
27
0
7
Order By: Relevance
“…A number of these beneficial factors have been supported in previous findings and have been found to positively affect the physical activity program [30, 31]. The findings of this study are also similar and support the notion that certain components of the program influenced the effectiveness of social interactions and communication for children with autism [30, 31].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A number of these beneficial factors have been supported in previous findings and have been found to positively affect the physical activity program [30, 31]. The findings of this study are also similar and support the notion that certain components of the program influenced the effectiveness of social interactions and communication for children with autism [30, 31].…”
Section: Discussionsupporting
confidence: 87%
“…The findings of this study are also similar and support the notion that certain components of the program influenced the effectiveness of social interactions and communication for children with autism [30, 31]. Moreover, it revealed that multiple strategies are influential in the success of a physical activity program for children with ASD.…”
Section: Discussionsupporting
confidence: 86%
“…Comparison of the strength of elbow and knee extension and flexion between young adults with ID and sedentary, non‐disabled individuals showed 35–40% lower strength levels for individuals with ID (Horvat et al, 1997). No difference between individuals with ID and able‐bodied individuals is reported with regard to flexibility (Frey et al, 1999), but there is a paucity of published information concerning this fitness component (Chanias et al, 1998).…”
mentioning
confidence: 99%
“…Regular training has positive and significant effects on their muscular endurance, cardiovascular endurance and strength (Chanias et al 1998). Furthermore, Hinckson et al (2013) have shown that children involved in training programs were able to manage their weight.…”
Section: Importance Of Physical Activity Interventionsmentioning
confidence: 98%